KECENDERUNGAN PEMILIHAN TOPIK DAN ANALISIS KESALAHAN PENULISAN JUDUL ESAI MAHASISWA JURUSAN ILMU HUKUM UNIVERSITAS ISLAM SULTAN AGUNG (SEBUAH KAJIAN MKU BAHASA INDONESIA) - Meilan Arsanti (PBSI, FKIP UNISSULA, Semarang, 2017)
Method used in this research was documentation of studentsâ€™ assignments. Result of the research indicated that students of Law Science department in Unissula preferred topics related to social problems, 28.12% of total 12 topics for 64 students. The rest topics were 7.81% about politics and government, 15.62% ofÂ corruption, 7.81% of health, 17.18% of education, 1.56% of economics, 28.12% of social, 0% of art and culture, 10.93% of law, 0% of technology, 0% of sports, and 7.81% of environment. Result of error analysis in writing essay title represented in a bar chart indicated that the errors were 10.93% on capital letter, 4.68% on words, 12.50% on words which are included as conjunctions (linking words), and 3.12% on punctuation. In the aspects of italic words writing, prepositions, repeated words and interjections (feeling exclamations), the errors were 0%. TotalÂ error was about 31.23% while the correct writing was 68.77%. Thus, it indicated that students of Law Science department, who mostly known to attach to legal issues, preferred to social topics happened in Indonesia. It was because they were freshmen who did not focus on legal issues yet. Social issues are often sensitive to legal issues. In writing essay title, the errors mostly done by students of Law Science department of Unissula were on conjunctions writing, such as using capital letters on conjunctions which should be written with small letters. Besides, the errors mostly happened when the students used capital letters on words which should be written in small letters.